PERHITUNGAN NILAI OVERALL EQUIPMENT EFFECTIVENESS PADA POMPA DISTRIBUSI KUBOTA DOUBLE SUCTION VOLUTE PUMP MODEL DV-L DI PT. ABC - Jamil, Rivaldi Abubakar; Muhammad Zakinura (Universitas Nusa Putra, 2020)
Evaluation of machine performance is certainly very necessary to improve company production performance, one of which can be done by knowing the value of performance effectiveness using the Overall Equipment Effectiveness (OEE) calculation. This research was conducted on the Kubota Double Suction Volute Pump Model DV-L centrifugal pump at PT. ABC. The purpose of this study is to determine the Overall Equipment Effectiveness (OEE) value based on availability, performance and rate of quality factors. To compare the company OEE values obtained with the Overall Equipment Effectiveness World Class standard and proceed with identifying six big losses and knowing the root causes of OEE values using a causal diagram. Calculations obtained an Availability value of 99,07%, Performance of 91,53% and Quality of 100% and an average OEE of 90,68%. It is known that the OEE value is at the OEE standard >85%, but the performance value of the pump is still below the JIPM performance standard of >95% so that corrective action can be taken to increase the performance value of the effectiveness of the clean water distribution process using the Kubota Double Secton Volute centrifugal pump Pump Model DV-L.